One-pot synthesis of silica-hybridized Ag2S–CuS nanocomposites with tunable nonlinear optical properties. (October 2015) - Ann Mary, K.A.; Unnikrishnan, N.V.; Philip, Reji
Graphical abstract: Highlights: Silica modified QDs of CuS and Ag2 S is developed at room temperature. Formation of Ag2 S/CuS nanocomposites is confirmed from XRD and FFT of HRTEM images. The concentration dependent growth of silica modified QDs is discussed. Nonlinear absorption observed in ns excitations is dominated by SA and ESA. Tuning of optical limiting efficiency is achieved with relative Ag2 S content. Abstract: In the present work we report a simple, facile route developed for preparing silica hybridized copper sulfide and silver sulfide quantum dots at room temperature. By adjusting the concentration of the precursors, Ag2 S can form Ag2 S–CuS nanocomposites which are self regulated in one pot. Their crystalline, structural and optical properties have been investigated in detail, and the optical limiting nature is studied from fluence-dependent transmittance measurements employing short (5 ns) laser pulses at 532 nm. Ag2 S nanoparticles are found to have large third order nonlinear optical coefficients with a relatively lower optical limiting threshold of 1.7 J cm −2, while the nonlinearity of the nanocomposites is found to lie in between that of Ag2 S and CuS nanoparticles. These results suggest pathways for designing good quality optical limiters with tunable optical limiting efficiencies by varying the constituent nanocrystal compositions.